Թյուրքական ցեղերի բնակեցումը հյուսիսարևելյան Հայաստանում Սեֆյանների օրոք (XVI-XVII դդ.) - Եսայան, Անդրանիկ
In northeastern Armenia, the demographic picture significantly changed since the 16th century, when the region was settled by different nomadic tribes. This policy was carried out by the Ottoman Empire and Sefevid Iran, whose goal was to have strong support of their rule in Armenia. The new inhabitants changed not only the demography and the religious structure of the region but also the Armenian toponyms. The muslimization of Armenians and their deportation to the Ottoman Empire and Sefevid Iran also played a major role in the demographic changes in northeastern Armenia. After the devastation of those Armenian territories, various tribes replaced the local inhabitants. At first they settled near the River Kur, while the Armenians moved to the mountains, but later on the nomads also occupied the mountainous territories for pasturing their livestock in summer. В северо-восточной Армении демографическая картина сильно изменилась начиная с 16-го века, когда в регионе появились различные кочевые племена. Важную роль сыграли Османская Империя и Сефевидская Персия, которые переселяли в Армению разные племена, чтобы иметь здесь прочную опору для своей власти. Под влиянием новых племен изменилась не только демографическая и религиозная картина, но также армянские топонимы стали заменяться турецкими и персидскими; большая часть их сохранилась до сих пор. В изменении демографии важную роль играло вероотступничество населения и переселение армян в Османскую Империю и Сефевидскую Персию. После опустошения армянских территорий там стали селиться различные племена. Поначалу они селились у реки Кура, а здешние армяне уходили в горы, но затем и горные регионы были захвачены кочевниками для выгона скота в летнее время.
Keywords: Հյուսիսարևելյան Հայաստան; Էթնոժողովրդագրություն